STRATEGI PENGEMBANGAN USAHA SATE BANDENG SEBAGAI MAKANAN KHAS BANTEN DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI KOTA SERANG - Ade Fauji; Yuni Veronika Ompusunggu; Ririn Brigita Brasa; Putri Mirnawati Hasibuan (Yayasan Education and Social Center, 2026)
Milkfish satay Micro, Small, and Medium Enterprises (MSMEs) are businesses with high economic and cultural potential. However, they face various obstacles such as limited product innovation, suboptimal digital marketing, and limited distribution networks. This community service activity aims to improve the performance of MSMEs producing Banten-style milkfish satay through product quality enhancement, digital marketing, distribution development, business partnerships, and human resource development. The method used is a participatory approach through the stages of needs identification, outreach, mentoring, and evaluation. The results of the activity indicate an increase in knowledge and understanding of business development strategies, digital marketing, and the importance of innovation and partnerships in increasing product competitiveness among entrepreneurs. This activity contributes to expanding market opportunities and supporting increased community income through the development of sustainable milkfish satay businesses.